Split-Marker Recombination for Efficient Targeted Deletion of Fungal Genes - Natalie L. Catlett; Bee-Na Lee; O. C. Yoder; B. Gillian Turgeon (Fungal Genetics Reports, 2003)
A commonly used method for fungal gene deletion is introduction of linear DNA consisting of a selectable marker gene flanked on both sides by short stretches of DNA that target a gene of interest (Wirsel et al 1996 Curr. Genet 29:241-249). Gene deletion in Cochliobolus heterostrophus and Gibberella zeae occurs efficiently with this approach. To facilitate deletion construct synthesis, we have applied the "split-marker” deletion strategy previously developed for Saccharomyces cerevisiae (Fairhead et al. 1996 Yeast 12:1439-57; Fairhead et al. 1998 Gene 223:33-46). Here, we describe both fusion PCR-based and plasmid-based deletion methods using this strategy with PEG-mediated protoplast transformation (Turgeon et al, 1985 Mol. Gen. Genet. 201:450-453). These methods are predicted to work well with any transformable fungus that undergoes homologous recombination between chromosomal and introduced DNA sequences.